Acute Perforated Appendicitis: A Case Report - Mohd. Nizam; Syafruddin Syafruddin (Jurnal Medika Nusantara, 2023)
Appendicitis is an inflammation that occurs in appendix vermicularis, a tubular organ located at the base of the large intestine located in the lower right abdomen, which acute inflammation of the appendix. Appendicitis is the most common case of acute abdominal surgery. Appendicitis can hit all age groups, although it is not common in children before school age. can causes dangerous complications if surgery is not performed immediately. The patient's history of the course of the disease and physical examination are the most important things in diagnosing appendicitis. All cases of appendicitis require the removal of the inflamed appendix, both with laparotomy and with laparoscopy. If treatment is not taken, the mortality rate will be high, mainly caused by peritonitis and shock. Here we present a case of acute perforated appendicitis in a 29-year-old male patient.